Physical properties of pectin-high amylose starch mixtures cross-linked with sodium trimetaphosphate - Carbinatto, Fernanda M. [UNESP]; Castro, Ana Doris de [UNESP]; Cury, Beatriz Stringhetti Ferreira [UNESP]; Magalhaes, Alvicler; Evangelista, Raul Cesar [UNESP] (Elsevier B.V., 2012)
Pectin-high amylose starch mixtures (1:4; 1:1; 4:1) were cross-linked at different degrees and characterized by rheological, thermal, X-ray diffraction and NMR analyses. For comparison, samples without cross-linker addition were also prepared and characterized. Although all samples behaved as gels, the results evidenced that the phosphorylation reaction promotes the network strengthening, resulting in covalent gels (highest critical stress, G' and recovery %). Likewise, cross-linked samples presented the highest thermal stability. However, alkaline treatment without cross-linker allowed a structural reorganization of samples, as they also behaved as covalent gels, but weaker than those gels from cross-linked samples, and presented higher thermal stability than the physical mixtures. X-ray diffractograms also evidenced the occurrence of physical and chemical modifications due to the cross-linking process and indicated that samples without cross-linker underwent some structural reorganization, resulting in a decrease of crystallinity. The chemical shift of resonance signals corroborates the occurrence of structural modifications by both alkaline treatment and cross-linking reaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: High amylose starch; Pectin; Cross-linking; Thermal analysis; Rheology; X-ray diffraction